(untitled) (Journal of Oriental Studies, 2016)
В статье на основе средневековых источниках, раскрывается внешняя политика Золотой Орды в годы правление Узбек хана. Автор характеризирует цель и значение внешняя политика Узбек хана в рекон- струкции политических событий в начале ХІV в. In this article on the basis of medieval Arabian and Persian sources, is considered the foreign policy of the Golden Horde during the reign of Uzbek khan. The author explains the purpose and value foreign policy the Uzbek of the khan in reconstruction of political events beginning ХІV century.